Foliar spraying melatonin reduces the threat of chromium-contaminated water to wheat production by improving photosynthesis, limiting Cr translocation and reducing oxidative stress - Chuanjiao Sun; Libing Xu; Qiang Gao; Shuzhen Sun; Xiaoxue Liu; Zigang Zhang; Zhongwei Tian; Tingbo Dai; Jianyun Sun (Ecotoxicology and Environmental Safety)
Chromium (Cr)-contaminated in irrigation water poses a significant threat to the safety of wheat (Triticum aestivum L.) production safety. Recent studies suggest that melatonin (MT) could enhance crop tolerance to Cr pollution. This study aimed to investigate the effects of foliar spraying MT on alleviating Cr toxicity and accumulation in wheat irrigated with K2Cr2O7 solution at concentrations of 5, 10, and 20 mg/kg Cr in the soil. Our results showed that Cr-contaminated water irrigation significantly reduced dry weight, grain numbers, grain weight, yield, harvest index, net photosynthetic rate (Pn), maximum and actual photochemical efficiency of photosystem II (Fv/Fm and ΦPSII), chlorophyll contents, and the a/b ratio. It also increased PSII photodamage and oxidative stress in wheat leaves, resulting in high Cr accumulation in roots, leaves, and grains. Foliar spraying of MT alleviated Cr toxicity by improving Pn, Fv/Fm, and ΦPSII, enhancing chlorophyll content, promoting dry matter accumulation and yield, and reducing oxidative stress and Cr translocation. Furthermore, MT application enhanced transcriptional regulation, alleviated oxidative stress by boosting antioxidant enzyme activities, and restricted Cr translocation from roots to leaves and grains by increasing the accumulation of secondary metabolites, such as lignin and metallothionein. These findings suggest that MT application could serve as a viable strategy for reducing Cr contamination in cereals and supporting phytoremediation efforts.